Mechanisms of snowboarding-related severe head injury: shear strain induced by the opposite-edge phenomenon - Nakaguchi, H.; Tsutsumi, K. (Journal of Neurosurgery, 2002)
Object. To date, there has been no published study in which the focus was on the mechanisms of head injuries associated with snowboarding. The purpose of this study was to identify these mechanisms.